Microcosms of Democracy? A Study of the Internal Governance of International NGOs in Kenya - LISTON, VANESSA (Taylor & Francis, 2009)
An assumption prevails within the international development community that direct exposure to democracy within civil society is a necessary condition for democratic political culture and hence democratic consolidation. International non-governmental organizations (NGOs) are considered key players in providing this direct exposure through the associational opportunities they provide and the democratic values they espouse. Yet, there is little empirical research on the internal governance of these organizations. Have they the potential to act as `schools of democracy? as postulated by de Tocqueville? Or do their governance structures reflect patterns of domination within the societies in which they are embedded? This paper presents the internal governance structures of 36 international NGOs in Kenya. Survey results show that the majority of NGOs occupy authoritarian or mid-range positions on a democracy/authoritarianism scale. This has wide implications for the democratic socialization possibilities of NGOs as well as the development paradigm in general.
PUBLISHED
Keywords: civil society; ngos; democracy; internal governance; africa; kenya